Variation, association and path analysis in finger millet (Eleusine coracana) under aerial moisture-stress condition - Thakur, S R; Saini, J P (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during summer season of 1989 and 1990 to study the variation, association and path analysis in finger millet [Eleusine coracana (L.) Geartn.] High heritability and genetic advance (% of mean) were observed respectively for yield (59%, 124%), days to flowering (80%, 17.4%), plant height (56%, 13.2%) and days to maturity (79%, 28.9%). Days to germination, heading and maturity Showed high negative association with grain yield, whereas fingers/plant showed high positive association. In addition, path analysis revealed the importance of tillers/plant. Thus per-se selection for yield would be highly effective, with simultaneous selection for lower days to germination, heading and maturity, and higher number of tillers and fingers/plant.